2018
DOI: 10.1186/s13075-018-1639-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional intraepithelial lymphocyte changes in inflammatory bowel disease and spondyloarthritis have disease specific correlations with intestinal microbiota

Abstract: BackgroundDysbiosis occurs in spondyloarthritis (SpA) and inflammatory bowel disease (IBD), which is subdivided into Crohn’s disease (CD) and ulcerative colitis (UC). The immunologic consequences of alterations in microbiota, however, have not been defined. Intraepithelial lymphocytes (IELs) are T cells within the intestinal epithelium that are in close contact with bacteria and are likely to be modulated by changes in microbiota. We examined differences in human gut-associated bacteria and tested correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 46 publications
2
27
0
2
Order By: Relevance
“…Furthermore, IELs regulate epithelial barrier integrity as they are the primary sensors of microbial antigens presented by epithelial cells and lamina propria macrophages 131,132 . A 2018 study suggested a decrease in IEL number in patients with axSpA compared with healthy individuals, but not in patients with Crohn's disease or ulcerative colitis 133 . In this study, IELs from patients with Crohn's disease and those with axSpA were found to produce increased levels of TNF, but only IELs from patients with Crohn's disease produced more IL-17 than healthy individuals.…”
Section: Immunological Alterations In Spamentioning
confidence: 99%
“…Furthermore, IELs regulate epithelial barrier integrity as they are the primary sensors of microbial antigens presented by epithelial cells and lamina propria macrophages 131,132 . A 2018 study suggested a decrease in IEL number in patients with axSpA compared with healthy individuals, but not in patients with Crohn's disease or ulcerative colitis 133 . In this study, IELs from patients with Crohn's disease and those with axSpA were found to produce increased levels of TNF, but only IELs from patients with Crohn's disease produced more IL-17 than healthy individuals.…”
Section: Immunological Alterations In Spamentioning
confidence: 99%
“…The first case study interrogates microbiome:cytokine relationships in fecal samples from HIV-negative high risk individuals and HIV-negative low risk individuals. The second case study uses published data, and identifies new findings in fecal microbiome:cytokine relationships in patients with spondyloarthritis, Crohn’s disease, ulcerative colitis, and healthy controls [30]. The third case study considers microbiome:immune cell relationships in gut biopsies in HIV-positive and HIV-negative participants.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Regner et al reported on relationships between the gut microbiome and cytokines produced by mitogen-stimulated intraepithelial lymphocytes (IEL) in patients with spondyloarthritis (SpA), Crohn’s disease (CD), ulcerative colitis (UC), and healthy controls (HC) [30]. Among other results, Regner identified elevated levels of TNFα in patients with SpA and CD.…”
Section: Resultsmentioning
confidence: 99%
“…The first case study interrogates microbiome:cytokine relationships in fecal samples from HIV-negative high risk individuals and HIVnegative low risk individuals. The second case study uses published data, and identifies new findings in fecal microbiome:cytokine relationships in patients with spondyloarthritis, Crohn's disease, ulcerative colitis, and healthy controls (29). The third case study considers microbiome:immune cell relationships in gut biopsies in HIV-positive and HIV-negative participants.…”
Section: Resultsmentioning
confidence: 99%